Reception: Covid-19 On-line Support Group Experience Report for the Bereaved - Bicalho reis, Luciana; Magalhães Gonçalves, Ana Luiza; da Silva Cajaiba, Karina; da Silva , Maiara; Rocha de Morais Fiorese, Aline; Brunetti Lambert, Carla; Augusta Magalhães Oziel , Rafaela (Guará Journal, 2023)
This article reports on the experience of extending online support groups to those bereaved by COVID-19. Ten weekly meetings were held with eight participants. The brief, focused approach aimed to help the bereaved resolve separation conflicts and facilitate their adaptation to grief. The activities were designed based on the group's needs and characteristics. Based on participants' accounts, it was clear that the support group constituted an important space for expressing and validating the emotions and feelings that make up the experience of grief, with the opportunity to learn about grief and build social and emotional support networks. During the pandemic, risk factors for more difficult grief experiences increase, such as multiple losses, lack of social support, and the absence of traditional farewell rituals. Proposals such as Acolhe(dor) can reduce the risks of complicated grief and produce positive effects on the mental health of the bereaved.